The politicisation of reconciliation in Zimbabwe : a case study of the Nkayi District - Wielenga, Cori (University of Pretoria, 2015)
In Zimbabwe, reconciliation has become a contentious process and has been politicised at the international, national and community levels. Criticisms have been raised against the government related to its failure to implement inclusive reconciliation processes that can amend broken relationships in Zimbabwe, particularly at the community level. Civil Society Organisations (CSOs) that are traditionally assumed to have a role in bringing about reconciliation on the community level have, in Zimbabwe, become part of the politicisation of reconciliation in various ways.